Speech by Hija de Perra at the 2013 march for sexual diversity in Arica (Revista Apotheke, 2023)
The text "Speech by Hija de Perra at the 2013 March for Sexual Diversity in Arica" is a speech given during a march in Arica, in 2013, in defense of sexual diversity. The speech was given by Hija de Perra, an activist and defender of LGBTQ+ rights. In her speech, Hija de Perra addresses the importance of the march and the fight for sexual diversity. She highlights the need for visibility and respect for LGBTQ+ people, who are often marginalized and discriminated against in society. Hija de Perra emphasizes that sexual diversity is a fundamental human right and that all people deserve to be treated with dignity and equality, regardless of their sexual orientation or gender identity. Furthermore, the activist criticizes the prejudice and violence that are often directed at LGBTQ+ people. She emphasizes the importance of combating homophobia, transphobia and all forms of discrimination, and defends the creation of public policies that promote inclusion and equality for the LGBTQ+ community. Hija de Perra also highlights the importance of unity and solidarity among LGBTQ+ people, as well as the need for alliances with other social groups and movements fighting for human rights. She concludes her speech by reaffirming her commitment to continue fighting for sexual diversity and the rights of LGBTQ+ people. In short, Hija de Perra's speech at the 2013 March for Sexual Diversity in Arica was a powerful demonstration in defense of LGBTQ+ rights and gender equality. Through her words, she highlighted the importance of visibility, respect and the fight against discrimination, reaffirming her commitment to continue fighting for sexual diversity and the rights of LGBTQ+ people.
Keywords: gender; sexual diversity; gender relations; LGBTQ+ rights